2013
DOI: 10.1007/s00244-013-9918-0
|View full text |Cite
|
Sign up to set email alerts
|

Baccharis trimera (Less.) DC as Genotoxicity Indicator of Exposure to Coal and Emissions from a Thermal Power Plant

Abstract: During coal combustion, hazardous elements are discharged that impair environmental quality. Plant cover is the first available surface for the atmospheric pollutants in terrestrial ecosystems. The aim of this study was to evaluate genotoxicity in the aqueous extract of the native plant, Baccharis trimera, exposed to coal and emissions from a thermal power plant (coal-fired power plant in Candiota, Brazil), correlating seasonality, wind tunnel predominance, and presence of inorganic elements. The presence of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…This suggests that elevations in total phenolics and total flavonoids can be considered as stress defense mechanisms in plants against pollution. Toxic agents can gradually build up in plants because they provide the first and vast available surface for bioaccumulation of these pollutants at concentrations substantially higher than the permissible values considered safe for human use [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that elevations in total phenolics and total flavonoids can be considered as stress defense mechanisms in plants against pollution. Toxic agents can gradually build up in plants because they provide the first and vast available surface for bioaccumulation of these pollutants at concentrations substantially higher than the permissible values considered safe for human use [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of humans to high levels of toxic agents constitutes a significant health risk [25]. Only a few studies on plants grown in polluted areas have been done to determine the toxic effects of pollutants [23,24]. In this study, the in vivo genotoxic potential of F. carica and S. molle grown in normal and polluted areas were investigated and compared.…”
Section: Discussionmentioning
confidence: 99%
“…Some animals that are bred in contaminated environments are directly exposed to these contaminants, but herbivores, such as the subterranean rodents analyzed in this study, can be exposed through contaminated food, as observed by Menezes et al . 31 in plants from Candiota, which had hight level of inorganic elements. Thus, these animals expose themselves to the contaminants in the soil and plants, in their microenvironment and in the atmosphere in regions with or without pollutants.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of PAH was found in its coal, bottom and fly ash samples 29 , metals were detected in soil samples 30 and Zn, Ni, Cu, Cd, V and Pb were detected in the tissues of the subterranean rodent C. torquatus 23 . In addition, studies with organisms have shown DNA damage in plants ( Baccharis trimera ) 9,31 , snail ( Helix aspersa ) 10 and coal workers’ blood 30,32,33 . To our knowledge, no previous studies have examined the effects of coal and its byproducts on telomere length or DNA global methylation in tuco-tuco.
Figure 1Geographic distribution of C. torquatus , which coincides with the geographic distribution of coal reserves and power plant Candiota (modified from Fernandes et al .
…”
Section: Introductionmentioning
confidence: 99%
“…The Cu content of 29.9 ± 14.5 ppm in PSAE is higher than that previously reported in studies of other medicinal plants, fruits, and juices [ 19 , 31 ]. Cu is used as a biomonitor for air pollution in plants, such as Baccharis sp., when exposed to polluted areas [ 32 ]. The excess intake of Cu may lead to neuropsychiatric symptoms such as those observed in Wilson's disease [ 33 ].…”
Section: Discussionmentioning
confidence: 99%